Large T Antigen-Specific Cytotoxic T Cells Protect Against Dendritic Cell Tumors through Perforin-Mediated Mechanisms Independent of CD4 T Cell Help - Duval, Anaïs; Fuertes Marraco, Silvia A.; Schwitter, Dominik; Leuenberger, Line; Acha-Orbea, Hans (Frontiers in Immunology, 2014)
Our newly generated murine tumor (MuTu) dendritic cell (DC) lines, generated from tumors developing in transgenic mice expressing the SV40 large T antigen and GFP under the DC specific promoter CD11c, reproduce the phenotypic and functional properties of splenic wild type CD8α+ conventional DCs. They have an immature phenotype with low co-stimulation molecule expression (CD40, CD70, CD80, CD86) that is upregulated after activation with toll-like receptor ligands. We observed, that after transfer into syngeneic C57BL/6 mice, MuTuDC lines were quickly rejected. Tumors grew efficiently in large T transgene-tolerant mice. To investigate the immune response towards the large T antigen that leads to rejection of the MuTuDC lines, they were genetically engineered by lentiviral transduction to express luciferase and tested for the induction of DC tumors after adoptive transfer in various gene deficient recipient mice. Here we document that the MuTuDC line was rejected in C57BL/6 mice by a CD4 T cell help-independent, perforin-mediated CD8 T cell response to the SV40 Large T antigen without pre-activation or co-injection of adjuvants. Using depleting anti-CD8β antibodies we were able to induce efficient tumor growth in C57BL/6 mice. These results are important for researchers who want to use the MuTuDC lines for in vivo studies.